2008
DOI: 10.1213/ane.0b013e318172f9e9
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Inhibition of Agonist-Induced Granulocyte-Platelet Aggregation After Low-Dose Sevoflurane Inhalation in Humans

Abstract: We demonstrated for the first time that inhaling low-dose sevoflurane (<1 vol % end-tidal) inhibits agonist-induced granulocyte-platelet interactions 24 h after administration and thus counteracts thromboinflammatory processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…21 The same low concentration inhibits agonist-induced granulocyte-platelet interactions up to 24 hours after administration and thus counteracts the thromboinflammatory processes. 22 Sevoflurane was found to be cardioprotective in patients undergoing cardiac surgery. [10][11][12][13] In the current study, we did not find a difference in the degree of myocardial injury between the sevoflurane and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…21 The same low concentration inhibits agonist-induced granulocyte-platelet interactions up to 24 hours after administration and thus counteracts the thromboinflammatory processes. 22 Sevoflurane was found to be cardioprotective in patients undergoing cardiac surgery. [10][11][12][13] In the current study, we did not find a difference in the degree of myocardial injury between the sevoflurane and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to comment on the clinical value of these changes due to our limited sample size, but further study is merited as sevoflurane has been shown to inhibit platelet aggregation induced by adenosine diphosphate [9,10].…”
Section: Discussionmentioning
confidence: 93%
“…Full anesthetic doses of halogenated ethers may not be required to see these effects, since sub-anesthetic doses can decrease plateletneutrophil interactions in human subjects. 11 With the use of any drug in in-vivo models, unintentional effects must be assumed, and controlling for these effects is difficult. Animals not receiving isoflurane received sodium pentobarbital as an anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…8 These volatile gasses are known to prevent neutrophil adhesion to the endothelium, 9,10 but the exact mechanism remains unclear. Recently, sub-anesthetic doses of sevoflurane have been shown to inhibit granulocyte-platelet interactions, 11 suggesting a possible reagent to uncouple coagulation and the maladaptive innate immunity in ALI/ARDS. Thus, platelets appear to have a role in the pathogenesis of ALI via a response to the initial insult resulting in neutrophil activation and release of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%